2022
DOI: 10.1101/2022.06.29.498168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prioritization of semantic over visuo-perceptual aspects in multi-item working memory

Abstract: Working Memory (WM) keeps information temporarily available for upcoming tasks. How the contents of WM are distinguished from perceptual representations on the one hand, and from long-term memories on the other, is still debated. Here, we leveraged recent evidence for a reversal of processing dynamics when retrieving episodic long-term memories as opposed to perceiving visual input. In two experiments (n=75 and n=103), we asked participants to hold one or more items in WM and to report their low-level perceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…An alternative framing of the cardinal repulsion biases in our experiment with real-life objects could be in terms of more explicit semantic categorization (e.g., "left"/"right" and "up"/"upside down"; Hardman et al, 2017;Ricker et al, 2022). The results may thus also reflect increased reliance on semantics (Kerrén et al, 2022) and/or (pre-)verbal labels when restoring information from unattended storage (see also Beukers et al, 2021), which would be in line with a higher level of abstraction. While our geometrical analysis approach is agnostic to the mechanistic cause of cardinal biases, we found some indications that they were also evident in biased gaze geometries during the stimulus-free retention periods (for related findings in neuroimaging, see Bae, 2021;Ester et al, 2020;Wolff et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An alternative framing of the cardinal repulsion biases in our experiment with real-life objects could be in terms of more explicit semantic categorization (e.g., "left"/"right" and "up"/"upside down"; Hardman et al, 2017;Ricker et al, 2022). The results may thus also reflect increased reliance on semantics (Kerrén et al, 2022) and/or (pre-)verbal labels when restoring information from unattended storage (see also Beukers et al, 2021), which would be in line with a higher level of abstraction. While our geometrical analysis approach is agnostic to the mechanistic cause of cardinal biases, we found some indications that they were also evident in biased gaze geometries during the stimulus-free retention periods (for related findings in neuroimaging, see Bae, 2021;Ester et al, 2020;Wolff et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…While unattended, WM contents cannot easily be decoded with neuroimaging approaches (but see Christophel et al, 2018), and the neural substrates of unattended storage remain disputed (Barbosa et al, 2021; Beukers et al, 2021; Stokes, 2015). Behaviorally, however, temporary inattention renders working memories less precise (Bae & Luck, 2018; Emrich et al, 2017) and more categorically biased (Bae & Luck, 2019), which may suggest increased abstraction of the WM content (see also Kerrén et al, 2022). Physiological evidence for when and how such modifications may occur during WM maintenance is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This notion has been recently supported by behavioral (Kerren et al, 2022) and neuroimaging (Kwak & Curtis, 2022) studies. In particular, (Kerren et al, 2022) demonstrated that semantic aspects of images are selectively prioritized during WM maintenance in a multi-item WM task, while no selective storage of abstract features of images is present in single-item tests. In the fMRI study of (Kwak & Curtis, 2022), on the other hand, representational abstraction was observed in parietal and visual cortices, but not in prefrontal regions.…”
Section: Discussionmentioning
confidence: 77%
“…With regard to Kerren et al (2022), we observed abstraction in the PFC even during maintenance of single items, while the VVS contained both perceptually detailed and abstract representations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation